Techniques of teaching strategies - Siddqui, Mujibul Hasan (India, 2005)
The book provides ideas for accommodations and specific instructional strategies for teaching spelling, reading, and writing language. It is geared to the professional teacher, especially those whose students might be contending with learning disabilities. In addition, it can be used by home-schooling parents and by parents of disabled students.
Keywords: Learning; Teaching Methods; Teaching Strategies; Teaching Techniques